2015
DOI: 10.1111/bjhp.12156
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil function in young and old caregivers

Abstract: What is already known on this subject? Ageing is accompanied by the decrease in innate and adaptive immunity, termed immunosenescence. Caregiving stress has been shown to exert negative effect on immune function in both young and old. What does this study add? The study examined effect of caregiving and ageing simultaneously in four groups of participants. Neutrophil function and stress hormone levels were preserved in the stressed in both age groups. Those with higher psychological morbidity had poorer neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…These deviations are most evident in older caregivers, but in younger individuals, this condition also leads to increased immune aging as indicated by advanced T cell differentiation. Although steady-state neutrophil anti-bacterial function appears not significantly different between caregivers and controls, those with higher psychological morbidity have poorer neutrophil phagocytosis capacity, suggesting decreased function of the cells under challenging conditions [53].…”
Section: Immune Consequences Of Stress Induced By Caregiving To Child...mentioning
confidence: 87%
“…These deviations are most evident in older caregivers, but in younger individuals, this condition also leads to increased immune aging as indicated by advanced T cell differentiation. Although steady-state neutrophil anti-bacterial function appears not significantly different between caregivers and controls, those with higher psychological morbidity have poorer neutrophil phagocytosis capacity, suggesting decreased function of the cells under challenging conditions [53].…”
Section: Immune Consequences Of Stress Induced By Caregiving To Child...mentioning
confidence: 87%
“…44 Furthermore, the reactive oxygen species produced by neutrophils has been reported to be reduced in the elderly. 45,46 The degranulation of neutrophils, associated with intracellular killing activity of neutrophils, was also impaired in the elderly. 47 However, due to the selection bias of age with 39 to 72 years in the UK Biobank, the age-dependent pattern in the correlation of neutrophil on ALS may need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…One could conclude that in the absence of immunosenescence, not all aspects of immunity are compromised, but it may be that specific aspects of caregiving not just the role per se are important influencers of immunity. For example, particular aspects of the caregiving experience may influence or accelerate immune ageing as studies showed increased caregiver burden in young and older caregivers [7] and parental stress in younger caregivers [8] related to poorer neutrophil phagocytosis (ingestion) and superoxide production [7] and more advanced T cell differentiation [8], both associated with immune ageing. Further, these findings highlight potential mechanisms by which some caregivers might report poorer health given that poor sleep quality [7], and less exercise, smoking, and an unbalanced diet, as well as higher BMI [6] related to immune outcomes across studies.…”
Section: Effects Of Caregiving Among Younger Caregivers -Specific Aspmentioning
confidence: 99%